2022
DOI: 10.3390/plants11192612
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction between Copper and Nitrogen-Uptake, Translocation, and Distribution in Rice Plant

Abstract: Interactions among nutrients have been widely recognized in plants and play important roles in crop growth and yield formation. However, the interplay of Cu and N in rice plants is not yet clear. In this study, rice plants were grown with different combinations of Cu and N supply. The effects of Cu-N interaction on the growth, yield production, Cu and N transport, and gene expression levels were analyzed. The results showed that the effect of N supply on rice growth and yield formation was more pronounced than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The study attributed these results to the benefits of adopting (100&80%) GWR levels, which increased root length and efficiency, leading to an increase in root exudates and a decrease in soil pH, resulting in notable improvements in water and nutrient absorption rates from the soil rhizosphere. This is supported by previous studies 75 77 . Additionally, under these conditions, a significant number of stomata were open, and applying Znfol allowed Zn molecules to penetrate leaves stomata, improving nutrient contents directly and quickly and compensating for the lack of nutrient absorption by the root.…”
Section: Discussionsupporting
confidence: 92%
“…The study attributed these results to the benefits of adopting (100&80%) GWR levels, which increased root length and efficiency, leading to an increase in root exudates and a decrease in soil pH, resulting in notable improvements in water and nutrient absorption rates from the soil rhizosphere. This is supported by previous studies 75 77 . Additionally, under these conditions, a significant number of stomata were open, and applying Znfol allowed Zn molecules to penetrate leaves stomata, improving nutrient contents directly and quickly and compensating for the lack of nutrient absorption by the root.…”
Section: Discussionsupporting
confidence: 92%
“…Cu is the trace element with the lowest concentration among the analyzed element concentrations. The details of element accumulation in various sorghum cultivars were detailed in Figure 2; the result was linked to (Cui et al, 2022); the study showed that plants' copper and nitrogen assimilation, translocation, and distribution could interact effectively, as was evidenced in Figure 3, the correlation between Cu and Zn, r (5) = 66, P = 20.…”
Section: Copper (Cu)mentioning
confidence: 88%
“…We further focus on copper and zinc micronutrients, both shown to exhibit synergistic interactions with nitrogen toward plant uptake. The presence of copper improved the uptake of N in rice plants by 9−30%, 25 while zinc was shown as an essential micronutrient that is the most commonly deficient in plants, particularly in high-pH soils. 26 Only a few scant examples of Cu and Zn sulfate urea cocrystals exist in the literature, and all of them were synthesized using crystallization from aqueous solutions.…”
Section: ■ Introductionmentioning
confidence: 99%